An Overview on Properties and Constituents of Cow’s Milk (International Journal of Innovative Research in Engineering & Management, 2023)
Milk is an exceptionally valuable basic  material due to its relative ease of conversion into a broad  range of goods. In certain instances, milk receives very  little processing, Heating processing to lengthen the  microbiological shelf life of the product and homogenized  to avoid fat segregation to prolong the physiological  storage lifetime. 2 extra well ways for coagulating dairy  are alkaline thrombosis for yoghurt and enzymes clotting  for cheeses. Milk might also be sprayed-dried or utilized  as a basis for isolating components such as proteins or  lipids. Milk, and products produced from it, have been the  focus of scientific research for almost a century as a  consequence of its extensive applications and usage in  human nutrition. This chapter provides a brief review of  the components and characteristics of milk, with a focus  on heat-induced changes in milk. This section focusses  mostly on cow 's milking; milking from additional  significant dairying animals differs in various ways from  cow 's milk, but is is within the the purview of this section.  To compare the components and characteristics of milk  from cows, buffaloes, goats, and sheep.
Keywords: Cow; Lactose; Milk; Protein